Organizational and Legal Issues of Prosecutor’s Supervision of Noncustodial Penalties’ Enforcement - Olegovich Antonov, Igor (2020)
The article deals with a set of issues related to the due course of law in the execution of punishments not related to isolation from society, and which have recently become widespread in the framework of the implementation of one of the directions of the state's policy in the field of combating crime - the expansion of types of punishments alternative to imprisonment. The author analyzes the powers of the prosecutor's office as a guarantor of compliance with the rule of law in the field of prosecutorial supervision, the purpose of which is, on the one hand, to identify, suppress and prevent violations of the law in the execution of criminal sentences and prevention of recurrence of crimes, and on the other, to respect the rights and legitimate interests of convicts.